Association between myosin heavy chain protein isoforms and intramuscular anabolic signaling following resistance exercise in trained men. Issue 1 (27th January 2015) - Gonzalez, Adam M.; Hoffman, Jay R.; Townsend, Jeremy R.; Jajtner, Adam R.; Wells, Adam J.; Beyer, Kyle S.; Willoughby, Darryn S.; Oliveira, Leonardo P.; Fukuda, David H.; Fragala, Maren S.; Stout, Jeffrey R.
Abstract: Resistance exercise stimulates an increase in muscle protein synthesis regulated by intracellular anabolic signaling molecules in a mammalian/mechanistic target of rapamycin (mTOR)‐dependent pathway. The purpose of this study was to investigate acute anabolic signaling responses in experienced, resistance‐trained men, and to examine the association between myosin heavy chain (MHC) isoform composition and the magnitude of anabolic signaling. Eight resistance‐trained men (24.9 ± 4.3 years; 91.2 ± 12.4 kg; 176.7 ± 8.0 cm; 13.3 ± 3.9 body fat %) performed a whole body, high‐volume resistance exercise protocol (REX) and a control protocol (CTL) in a balanced, randomized order. Participants were provided a standardized breakfast, recovery drink, and meal during each protocol. Fine needle muscle biopsies were completed at baseline (BL), 2 h (2H) and 6 h post‐exercise (6H). BL biopsies were analyzed for MHC isoform composition. Phosphorylation of proteins specific to the Akt/mTOR signaling pathway and MHC mRNA expression was quantified. Phosphorylation of p70S6k was significantly greater in REX compared to CTL at 2H ( P = 0.04). MHC mRNA expression and other targets in the Akt/mTOR pathway were not significantly influenced by REX. The percentage of type IIX isoform was inversely correlated ( P < 0.05) with type I and type IIA MHC mRNA expression ( r = −0.69 to −0.93). Maximal strength was also observed to be inversely correlated ( P < 0.05) with Type I and Type IIA MHC mRNA expression ( r = −0.75 to −0.77) and p70S6k phosphorylation ( r = −0.75). Results indicate that activation of p70S6k occurs within 2‐h following REX in experienced, resistance‐trained men. Further, results also suggest that highly trained, stronger individuals have an attenuated acute anabolic response. Abstract : e12268 Resistance exercise stimulates an increase in muscle protein synthesis regulated by intracellular anabolic signaling molecules in a mammalian/mechanistic target of rapamycin (mTOR)‐dependent pathway. Results indicate that activation of p70S6k occurs within 2‐h following REX in experienced, resistance‐trained men. Further, results also suggest that highly trained, stronger individuals have an attenuated acute anabolic response.